Respuesta :

Answer:

x2+(3-2)x-6

x2+3x-2x-6

x(x+3)-2(x+3)

(x+3)(x-2)

its very easy please follow me and mark as brainliest i will solve your all problems of mathematics

x^+(3-2)x-6

x^+3x-2x-6

x(x+3)-2(x+3)

(x-2) (x+3)

Here there is x^+x-6 you have to mutiply x^ and 6

you will get 6x^.Then in the middle there is x so to bring x in the middle we have to think factors of 3 like 3×2=6 here 3-2=1 now we have get 1 that means x.

Now you will mutilpy 3-2 by x than you have to take common. Remember in this lesson if there is (- + = +) (- - = -) and (+ - = -) search in your book you will you will find it.

ACCESS MORE